Differences in US-German Time-Allocation: Why Do Americans Work Longer Hours than Germans? - Ronald Schettkat (Institute for the Study of Labor (IZA), 2003)
The conventional view is that Americans work longer hours than Germans and other Europeans but when time in household production is included, overall working time is very similar on both sides of the Atlantic. Americans spend more time on market work but German invest more in household production. This paper examines whether these differences in the allocation of time can be explained by differences in the incentive structure, this is by the taxwedge and differences in the wage differentials, as economic theory suggests. Its analysis of unique time-use data reveals that the differences in time-allocation patterns can indeed be explained by economic variables.
Keywords: D12; J22; H31; D13; 330; time use; working hours; employment; household production; Arbeitszeit; Hausarbeit; Zeitallokation; Haushaltsproduktion; Steuerbelastung; Lohnstruktur; Vereinigte Staaten; Deutschland